Different renoprotective effects of luseogliflozin depend on the renal function at the baseline in patients with type 2 diabetes: A retrospective study during 12 months before and after initiation. - Hiroyuki Ito; Suzuko Matsumoto; Takuma Izutsu; Eiji Kusano; Jiro Kondo; Hideyuki Inoue; Shinichi Antoku; Tomoko Yamasaki; Toshiko Mori; Michiko Togane (PLoS ONE)
Aims The safety and efficacy, particularly, the factors associated with the renal prognosis, were assessed over 12 months after the initiation of luseogliflozin therapy in Japanese patients with type 2 diabetes and renal impairment. Methods In total, 238 patients treated with luseogliflozin (2.5 mg, once daily) were studied as the safety analysis set. Two hundred and two subjects whose medication was continued over 12 months were investigated as the full analysis set. The subjects were divided into 3 groups based on the estimated glomerular filtration rate (eGFR): high eGFR (n = 49), normal eGFR (n = 116) and low eGFR (n = 37) groups. Results The body weight, systolic blood pressure, HbA1c and urinary protein excretion gradually decreased from baseline in all eGFR groups. While the eGFR was significantly reduced from baseline in the high and normal eGFR groups, the eGFR did not significantly differ over time in the low eGFR group. There was no marked difference in the frequency of adverse events that were specific for SGLT2 inhibitors among the 3 groups in the safety analysis set. Conclusions Luseogliflozin can preserve the renal function in the medium term in patients with type 2 diabetes and renal impairment without an increase in specific adverse events.